Volume 5: Turbo Expo 2004, Parts a and B 2004
DOI: 10.1115/gt2004-53867
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tip-Leakage Vortices and Passage Shock in Stall Inception in a Swept Transonic Compressor Rotor

Abstract: The current paper reports on investigations aimed at advancing the understanding of the flow field near the casing of a forward-swept transonic compressor rotor. The role of tip clearance flow and its interaction with the passage shock on stall inception are analyzed in detail. Steady and unsteady three-dimensional viscous flow calculations are applied to obtain flow fields at various operating conditions. The numerical results are first compared with available measured data. Then, the numerically obtained flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 16 publications
0
50
0
Order By: Relevance
“…Recently, the mechanism of stall inception has been discussed in two main aspects, the tip clearance flow characteristic and the stall developmental process, see Hah et al (2006), He (1997), Hoying et al (1999), Hah et al (1999Hah et al ( , 2004, Furukawa et al (2000), Yamada et al (2007). It is well known that the experiment is the most straightforward way for researching.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the mechanism of stall inception has been discussed in two main aspects, the tip clearance flow characteristic and the stall developmental process, see Hah et al (2006), He (1997), Hoying et al (1999), Hah et al (1999Hah et al ( , 2004, Furukawa et al (2000), Yamada et al (2007). It is well known that the experiment is the most straightforward way for researching.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum or peak compressor pressure ratio thus defines the stability limit. Numerical studies of axial compressors [18,19] showed that this criterion gives good results in predicting compressor stall. Centrifugal compressors may be able to operate into the left of the peak pressure ratio, but compressors will be in minor surge in this condition [20], and compressor outlet and inlet flow conditions will be pulsating and unsteady.…”
Section: Autoregressive Modelmentioning
confidence: 99%
“…Many experimental and numerical works can be found in the literature on the design and analysis of three-dimensional shaped transonic bladings (e.g. Copenhaver et al, 1996;Hah et al, 2004;. Fig.…”
Section: Three-dimensional Shaped Bladingsmentioning
confidence: 99%